O uso do inglês no processo de mediação da informação em contexto especializado: Desafios encontrados no cotidiano bibliotecário - ARAUJO, Brenda Lorena Câmara de (2019)
Presents the librarian's connection with the English language in the globalization, presenting data that ratify the foundation of the research; the importance of mastering this language in scientific communication, identifying key points such as the production, dissemination and transformation of information in English; the difficulties that the Librarian finds to carry out the mediation of the information in English and to serve the user who needs the information, in order to show the importance of knowing another language in times of change and large-scale document production, as observed in the present day. In addition to conducting an analysis in a research institution that works directly with the production and dissemination of scientific information worldwide: Universidade Federal do Pará, using as methodological procedures the basic or fundamental research to collect the data of what has already been explained on the subject, as well as a field research, with a questionnaire. The results confirmed the presupposition in the introduction of the work, so that the conclusions verified the importance of the English language for Librarians.